Optimisation of chloroquine phosphate loaded nanostructured lipid carriers using Box–Behnken design and its antimalarial efficacy. (9th August 2018) - Baruah, Uday Krishna; Gowthamarajan, Kuppusamy; Ravisankar, Vanka; Karri, Veera Venkata Satyanarayana Reddy; Simhadri, Praveen Kumar; Singh, Vineeta
Abstract: Chloroquine was once the most widely used antimalarial for nearly eight decades for its safety, efficiency, stability, low cost and finally for its less toxic nature. But its use and efficacy got slowly decreased with the increase of chloroquine resistant strains of Plasmodium species throughout the world. Lipid based nanodrug delivery systems have been very popular in the recent times as they are very less toxic, have drug targeting capabilities and also reduces the dosing frequency by increasing efficacy of the drug. In the present research work, response surface methodology was employed to optimise chloroquine phosphate (CQ) loaded nanostructured lipid carriers (NLCs) using a modified double emulsion technique. The optimised CQ loaded NLC showed a particle size of 66.50 ± 1.21 nm, PDI of 0.210 ± 0.016, ZP of +38.4 ± 1.44 and EE of 78.2 ± 1.2%, respectively. The in vitro and in vivo antimalarial studies of CQ loaded NLCs showed an enhanced antimalarial efficacy of the nanoformulation with a better suppression of parasitemia and with an increased efficacy of more than 23% in comparison to pure drug. This study demonstrated that by loading a drug into an NLCs system can help in overcoming the problems associated with the present antimalarials available.